Estrategias didácticas de enseñanza-aprendizaje, perspectiva estudiantil en carreras de negocios: estudio comparativo universidad colombiana- ecuatoriana - Solarte Solarte, Claudia; Bolaños Delgado, Sandra; Fonseca Romero, Gabriela; Esparza Paz, Fernando (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December)DO - 10.36779/mktdescubre/v#.#, 2019)
The role of the teacher at the university level went from teaching their students to let them learn, in this context educational strategies play a fundamental role in the educational training process. Evaluate how the application of educational strategies allows improving teaching and learning in students of business careers, conducting a comparative study in two Latin American universities, is the objective of the scientific article. The study design has a cross-sectional investigation, with a qualitative and quantitative approach, with a descriptive level scope; A documentary and field investigation was carried out through the use of surveys applied to university students of business careers at the CESMAG University (Nariño - Colombia) and Polytechnic School of Chimborazo (Riobamba - Ecuador), carried out the first half of the year 2019 The results revealed that the didactic strategies used in the classroom allow teachers a performance between excellent and very good, in the CESMAG University (77%) and in the ESPOCH (70%), through the application of didactic strategies. Therefore, it is concluded that educational strategies are transversal variables that help to improve the educational process in support of students.